2017
DOI: 10.1515/tjb-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CTLA-4 and CD28 gene variants and circulating protein levels in patients with gastric cancer

Abstract: Objective:Gastric cancer is one of the most common malignancies worldwide. The risk factors for gastric cancer include environmental and genetic factors. Inflammation and the immune system are known to contribute to the development of the gastric cancer. We examined the influence of critical polymorphisms of CTLA-4 and CD28 genes and circulating protein levels on the etiology of gastric cancer.Methods:Genotyping of SNPs was performed in 55 gastric cancer patients and 105 healthy individuals using the PCR-RFLP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The basic information and quality evaluation (NOS) results included in the study are shown in Table 1 . The included studies looked at cancer patients in Asia (n=6) [ 9 , 12 , 13 , 21 , 29 , 30 ] and Caucasians (n=13) [ 14 , 15 , 18 – 20 , 22 – 28 , 31 ]. In addition, in terms of cancer types, leukemia (n=2) [ 12 , 26 ], breast cancer (n=3) [ 9 , 13 , 15 ], colorectal cancer (n=3) [20,27,30)], cervical cancer (n=4) [ 21 23 , 28 ], and other cancers (prostate cancer, gastric cancer, renal cell carcinoma, non-small-cell lung cancer, melanoma, myeloma, lymphoma) were included in studies [ 4 , 9 , 14 , 18 , 25 , 29 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The basic information and quality evaluation (NOS) results included in the study are shown in Table 1 . The included studies looked at cancer patients in Asia (n=6) [ 9 , 12 , 13 , 21 , 29 , 30 ] and Caucasians (n=13) [ 14 , 15 , 18 – 20 , 22 – 28 , 31 ]. In addition, in terms of cancer types, leukemia (n=2) [ 12 , 26 ], breast cancer (n=3) [ 9 , 13 , 15 ], colorectal cancer (n=3) [20,27,30)], cervical cancer (n=4) [ 21 23 , 28 ], and other cancers (prostate cancer, gastric cancer, renal cell carcinoma, non-small-cell lung cancer, melanoma, myeloma, lymphoma) were included in studies [ 4 , 9 , 14 , 18 , 25 , 29 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a study performed in Iran did not find statistically significant differences in the genotype distribution and allele frequencies among CRC patients and controls [ 56 ]. In addition, in a Turkish population showed no significant association between rs231775 and the risk of gastric cancer [ 57 ]. Two meta-analyses found similar results regarding the rs231775 variant, showing an associated risk for cancer development even through subgroup analysis by type and ethnicity suggesting that CTLA-4 rs231775 is a key variant that could be associated with cancer development [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4 is a negative regulator of T-cell function and modulates the duration and strength of T cell mediated immune responses through several intrinsic and extrinsic mechanisms, triggering anergy and immune tolerance (27,28). Several studies have reported significant associations between frequent CTL4 polymorphisms and cancer susceptibility, including CRC (11,(29)(30)(31)(32)(33)(34)(35). We identified a positive association between CTL4 c.-319C > T (rs5742909) and CRC susceptibility (dominant genetic model, p = 0.023).…”
Section: Discussionmentioning
confidence: 99%